2004
DOI: 10.1111/j.1464-5491.2004.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and course of Type 2 diabetes in youth in a large multi‐ethnic city

Abstract: We report a similar increase in T2DM incidence and clinical presentation at HSC to other clinic reports in large North American urban centres. Of note is the high prevalence of children of South/South-East Asian descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 27 publications
2
80
0
Order By: Relevance
“…A recent study in children and adolescents with non‐alcoholic fatty liver disease reported a prevalence of impaired glucose tolerance of 23.4% and of Type 2 diabetes of 6.5% 27. Our finding of hypertension in 21% of children at diagnosis is consistent with other studies, which have reported rates of hypertension in adolescents of 10–55% at diagnosis 28, 29, although it was lower than the 34% rate reported in the 2005 cohort 30. In 11 cases no blood pressure data were available, therefore, cases of hypertension may have been missed.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in children and adolescents with non‐alcoholic fatty liver disease reported a prevalence of impaired glucose tolerance of 23.4% and of Type 2 diabetes of 6.5% 27. Our finding of hypertension in 21% of children at diagnosis is consistent with other studies, which have reported rates of hypertension in adolescents of 10–55% at diagnosis 28, 29, although it was lower than the 34% rate reported in the 2005 cohort 30. In 11 cases no blood pressure data were available, therefore, cases of hypertension may have been missed.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly the case in the USA [1, 2], but has also been reported in other countries [3,4,5]. The yearly number of newly documented manifestations of T2DM in children and adolescents has increased from 7 in 1992 to 38 in 2003 in standardized prospective documentation of children and adolescents with diabetes mellitus (dpv) in Germany and Austria [6].…”
Section: Introductionmentioning
confidence: 96%
“…Estimates of DKA prevalence at onset with type 2 diabetes vary substantially, from 41.4% and 16% among African-American youth in Cincinnati 14 and Arkansas, respectively, 13 to 8% among African Canadians and Southeast Asians in Toronto, 11 and 4.2% among Canadian Aboriginal youth. 12 We found that a higher prevalence of DKA was associated with younger age, minority race/ ethnicity, and male gender.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…5 It has been reported to be present in 25% to 30% of type 1 diabetes cases at onset [6][7][8][9][10] and from 4% to 29% in youth with type 2 diabetes, depending on race/ethnicity. [10][11][12][13][14] SEARCH previously reported that the prevalence of DKA at diagnosis was 25.5% in 2002-2003. 10 It is not known whether the presence of DKA at diagnosis has changed over time.…”
mentioning
confidence: 99%